2006
DOI: 10.1016/j.clpt.2005.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic variability of warfarin maintenance requirement is explained by VKORC1 genotype in an Asian population

Abstract: Interethnic difference in VKORC1 haplotypes accounts for the difference in warfarin requirements between Chinese, Malays, and Indians, providing interesting insights into genetic variation between ethnogeographically distinct Asian groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
107
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 36 publications
11
107
0
Order By: Relevance
“…69,71 Furthermore, a number of studies have shown that common SNPs in VKORC1 are strongly associated with warfarin maintenance dose in several populations (Table 3). [72][73][74][75][76][77][78][79][80][81][82][83] Additionally, a similar relationship has been demonstrated with the other vitamin K antagonists acenocoumarol and phenprocoumon, 84,85 with one study suggesting an association with coumarin-related bleeding. 85 The associated VKORC1 SNPs are within a region of strong linkage disequilibrium, and a combination of several SNPs does not contribute greater information than one individual SNP.…”
Section: The Vitamin K Cyclementioning
confidence: 70%
See 1 more Smart Citation
“…69,71 Furthermore, a number of studies have shown that common SNPs in VKORC1 are strongly associated with warfarin maintenance dose in several populations (Table 3). [72][73][74][75][76][77][78][79][80][81][82][83] Additionally, a similar relationship has been demonstrated with the other vitamin K antagonists acenocoumarol and phenprocoumon, 84,85 with one study suggesting an association with coumarin-related bleeding. 85 The associated VKORC1 SNPs are within a region of strong linkage disequilibrium, and a combination of several SNPs does not contribute greater information than one individual SNP.…”
Section: The Vitamin K Cyclementioning
confidence: 70%
“…Polymorphisms in the VKORC1 and CYP2C9 genes and a limited subset of environmental determinants account for around 50-60% of the variance in warfarin dose requirement. 73,76,77,79,[81][82][83] In six studies, the relative contribution of VKORC1 is greater than that of CYP2C9, 73,74,78,[81][82][83] in two, CYP2C9 has a greater quantitative contribution, 72,76 whereas VKORC1 and CYP2C9 contribute equally in one study. 79 Sconce et al 76 have gone on to develop a dosing table based on a regression equation combining age, height and CYP2C9*2 and CYP2C9*3, and the VKORC1 SNP À1639G4A.…”
Section: Future Challenges For Clinical Practicementioning
confidence: 99%
“…The dose requirements of oral anticoagulants were also found to be in accordance with the trend shown by the genotypes [13]. In a study involving Chinese, Malay and Indians living in Singapore [14], the mean weight-normalized COA dose was lower for Chinese and Malays than for Indians. In our study, we genotyped 180 patients of northern Indian origin, who were on COA therapy with stabilized INR range values between 2.0 and 3.5, for VKORC1 -1639 G [ A polymorphism and observed that the VKORC1 -1639G [ A minor allele frequency in the northern Indian patient group was 22% [10].…”
Section: Genetic Variants In Components Of the Coagulation Cascadementioning
confidence: 60%
“…[24][25][26] In the Singapore populations, the Indians were observed to display warfarin resistance, thus requiring a higher dose as compared with the Chinese and Malays. [26][27][28][29] There is no significant difference in ROH frequencies among the populations (ROH frequencies of 21, 13 and 20% for the Chinese, Malays and Indians, respectively). However, if we examine the haplotypes in this region, there is significant difference.…”
Section: Frequency Of Rohs and Frequency Of Haplotypes Within Rohsmentioning
confidence: 99%